Strategi Penanganan Pengaduan Masyarakat (Dumas) Guna Meningkatkan Profesionalisme Anggota Polri: Strategi Penanganan Pengaduan Masyarakat (Dumas) Guna Meningkatkan Profesionalisme Anggota Polri - Aziz, M Asrul; Suprapto, Heri (Jurnal Litbang Polri, 2023)
From a public complaint perspective, according to the Ombudsman, the Indonesian National Police is one of the public service delivery agencies that "subscribes" to complaints. In fact, in the last few years Polri has always been in the top 8 to 5 nationally as the institution with which the most complaints have been made. To overcome this, the National Police Chief, General Listyo Sigit Prabowo, included 5 priority programs related to public services and handling public complaints among the 16 National Police Chief Priority Programs. Then on February 24, 2021 the National Police Chief also launched the Dumas Precision application and to further emphasize the importance of cross-functional and sectoral cooperation and synergy regarding handling public complaints, the Indonesian National Police Chief issued a Chief of Police Circular Number: SE/5/II/2021 dated February 24, 2021 concerning the National Police System. Information on Integrated Community Complaint Handling within the National Police. This research was conducted in 11 Polda and 54 Polres. Data collection was carried out by distributing questionnaires to people who had made complaints to the National Police and Dumas operators, FGD with key officials at the Polda and Polres, as well as FGD with operators of public complaint services. The results of the study show that the responsiveness, trustworthiness, transparency and accountability of public complaint services by the Police are at a moderate level. There are still many personnel, both in Polda and Polres, who do not understand the concept of the Integrated Dumas Service Center (SPDT) and its implementation. The majority of Polri personnel who were complained about/didumas complained about the occurrence of repeated examinations/holdings of cases with the same case, both by internal and external parties. In fact, many personnel still have to undergo inspections, even though the handling of the Dumas has been completed